An investigation into the accuracy of the direction of the qibla in three historical mosques in Edirne, Turkey - Pirti, AtÄ±nÃ§; HoÅŸbaÅŸ, Ramazan GÃ¼rsel (Universitas Islam Negeri Alauddin Makassar, 2023)
For all Muslims it is important to pray in a specific direction, this is known as the qibla. The qibla direction of a mosque is generally determined using the qibla azimuth angle and qibla bearing angle which are calculated from the geographical coordinates of the Ka’ba Mosque in Mecca, Saudi Arabia and the place where the mosque is built. The door which is placed in the gallery of a minaret usually shows the qibla direction. In order to determine the accuracy of the direction the two horizontal edge coordinates of the door are required. This study has two important theoretical aspects. One concern measuring the qibla azimuth angle and qibla bearing angle and the other is related to the qibla direction shown by the minaret door. An experimental technique was carried out on the minaret doors of three historical mosques (Selimiye, Ancient and Three gallery of minarets Mosques) in Edirne, Turkey. The country coordinates of the corner points of each mosque were transformed into geographical coordinates, the qibla azimuth angles and the qibla bearing angles were calculated. The differences between the calculated qibla bearing angles and the qibla bearing angles shown by each door of the three mosque’s minarets are examined and interpreted. This type of study has not been performed in Turkey and also has importance for archaeological work.